The Shariah and Law Education in Malaysia in the Context of Legal Practice - Norfadhilah Mohamad Ali; Shah, HAR; Shukor, SA; Mutalib, LA; Salleh, AZ; Majid, MNA; Rusli, MHM; Amin, AUM; Nor, MM (Amer Scientific Publishers, 2024)
Indexed by WOS/ERA